The injury effect of osteopontin in sepsis-associated lung injury - Qian Wang; Zhicai Yu; Zhixin Song; Xue Lu; Zhu Li; Dandan Pi; Jing Li; Feng Xu (Journal of Inflammation)
Abstract Background Sepsis is a severe condition causing organ failure due to an abnormal immune reaction to infection, characterized by ongoing excessive inflammation and immune system issues. Osteopontin (OPN) is secreted by various cells and plays a crucial role in inflammatory responses and immune regulation. Nonetheless, the precise function of OPN in sepsis remains to be elucidated. Methods In the present study, we evaluated the levels of OPN in paediatric patients with sepsis and healthy individuals. We examined the impact of OPN on survival rates, systemic inflammation, and lung injury within an experimental sepsis model using cecal ligation and puncture (CLP). Furthermore, the pro-inflammatory effects and potential mechanisms of OPN in sepsis were investigated through Mouse Hemophagocytic Synuclein (MH-S) cells. Results The OPN level was found to be elevated in patients with sepsis (368.5 ± 249.4 ng/ml) compared to children with infections (73.78 ± 40.46 ng/ml) (p < 0.0001) and healthy individuals (44.03 ± 20.76 ng/ml) (p < 0.0001). The serum concentration of OPN was elevated in pediatric patients with septic shock compared to those with sepsis (504 ± 266.3 ng/ml vs. 238.6 ± 143.8 ng/ml, p < 0.001). Intravenous administration of OPN inhibitor into the tail vein decreased the mortality rate (HR = 0.2695, p = 0.0015), suppressed systemic inflammatory responses and mitigated lung tissue damage. The concentration of tumour necrosis factor (TNF)-α, IL-6 and IL-1β in serum of CLP mice treated with OPN inhibitor decreased compared with CLP mice. Within the sepsis mouse model, there was a marked increase in OPN expression in the lung’s tissues compared to the sham group mice. This surge was accompanied by a significant accumulation of alveolar macrophages and an upregulation of inflammasome expression. Mechanistic investigations in MH-s cells revealed that OPN-siRNA suppressed the LPS-induced macrophage inflammatory response by inhibiting caspase1-dependent classical pyroptosis signaling pathway. However, recombinant OPN was supplemented after OPN silencing, the protective effects in MH-s cells treated with LPS were reversed. Conclusion This study reveals that OPN has an adverse impact on the host’s immune response to sepsis. Suppressing OPN expression holds potential therapeutic value for the treatment of sepsis. Trial registration Study on the diagnostic value of osteopontin in children with sepsis. MR5024001771. Registered 22 January 2024. https//www.medicalresearch.org.cn.